Analysis of the spread of Flavescence dorée-related phytoplasmas in naturally infected alder in Germany based on molecular and geodata - Jarausch, Wolfgang; Runne, Miriam; Schell, Tanja; Guerniche, Djamal; Jarausch, Barbara; Trapp, Matthias (Frontiers in Agronomy, 2025)
IntroductionFlavescence dorée (FD) is a European quarantine disease of grapevine with high economic impact. The Flavescence dorée phytoplasmas (FDp) are epidemically spread by the leafhopper Scaphoideus titanus, which has been introduced to Europe from North America. The FDp is of European origin and is widely spread in symptomless alder trees. FD outbreaks were related to three different genetic variants of FDp: MAP-FD1, MAP-FD2 and MAP-FD3. A multitude of non-epidemic genotypes exist in mixed infections in alder trees. Germany is so far free of FD but the possibility of the transmission of MAP-FD2 phytoplasmas from alder to grapevine by the invasive secondary vector Orientus ishidae has been demonstrated experimentally and under natural conditions. Thus, FDp-infected alder represent a risk for FD outbreaks.MethodsGeodata-based analyses were employed to identify potential alder sites adjacent to vineyards in the major wine-growing regions of Germany in Rhineland-Palatinate and Baden-Wuerttemberg. Webmaps for Plant Protection Services were established. In addition, molecular screening tools for the detection of MAP-FD1 and MAP-FD2 phytoplasmas in mixed infections in alders were developed.Results and Discussion1089 alder samples from 171 sites in Rhineland-Palatinate, 556 alder samples from 104 sites in Baden-Wuerttemberg and 141 samples from 22 sites in Franconia were examined. Almost all samples (98%) were infected with 16SrV phytoplasmas. The distribution of MAP-FD2 phytoplasmas varied greatly among the different regions: no infections were found in the Mosel-Saar-Ruwer region while along the Rhine valley from Rheinhessen to Baden infection rates around 70% were observed. Northern and Southern regions of Baden-Wuerttemberg as well as Franconia had lower infection rates ranging from 15% to 40%. Insect captures in the different regions showed that O. ishidae is present in all regions but infection rates varied indicating that this invasive species is responsible for the spread of MAP-FD2 phytoplasma in alder in Germany. Only few infections with MAP-FD1 genotypes were found. Specific primers for the epidemic map genotype M54 revealed no infection in the alder trees.